QUALITY OF COPRA MANUFACTURED FROM SUB-STANDARD NUTS - S B. Ratnayake' (International Coconut Community, 1999)
It is well known that copra manufactured from substandard nuts are invariably of poor quality. The reasons that lead to or poor quality are varied, depending on the nature of the defect of the raw material. However, a better understanding of the parameters that cause poor quality can lead to attainment of considerable advantages, through minimization of losses arising from deterioration of quality of the product. Though the copra manufactured out of substandard raw material may not strictly meet with the standards of up-market grades such as